Transmission effect of international grain prices on China’s grain prices - Chiming Qi; Chang Meng; Shuo Yan (Frontiers in Sustainable Food Systems)
With the rapid development of China’s economy, people’s living standards and food requirements have also changed. Grain imports have significantly increased to meet the growing demand for food, which has increased the transmission effect between international and domestic grain prices and exposed the nation’s food security to greater risk. Therefore, this study aims to investigate the price transmission mechanism and its impact on food security in China. It utilizes data on the spot and futures prices of major international grains from 2013 to 2020, along with an analysis of the corn stockpiling system reform through a quasi-natural experiment. The results indicate that different grain varieties exhibit distinct supply and demand structures, while the degree to which they are affected by international prices varies significantly. Grains with higher levels of marketization and openness are more susceptible to fluctuations in international market prices. This transmission effect is closely related to the total import volume of the agricultural product and its substitutes. The soybean market, the most marketized and open market in China, is influenced by international prices the most significantly. Furthermore, corn prices have become more sensitive to international markets, especially since the reform of the stockpiling system, which has increased marketization. By contrast, as the main staples in China, wheat and rice are less affected by fluctuations in international market prices due to low marketization and openness. This study finds that the transmission mechanism between domestic and foreign grain markets is mainly established through international trade. It provides new empirical evidence for global price transmission theory and promotes international trade theory. In practice, the findings will assist in managing the effects of international grain price fluctuations on the domestic grain market as well as in formulating future policies to more effectively ensure a stable domestic grain supply.